Pengaruh Efektivitas Penerapan Sistem Informasi Pengelolaan Keuangan Daerah (SIPKD) Terhadap Kualitas Laporan Keuangan di Pemerintah Kota Denpasar - dewi, ayu ratna; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2014)
The implementation of information systems, particularly in government agencies, have  a considerable role in generating quality financial statements. The government is trying to realize the excellent service to the community by building information technology in finance or accounting in relation to the financial management area. The purpose of this study was to determine the level of effectiveness of the Financial Management Information System (SIPKD) and its influence on the quality of financial reporting in the City of Denpasar. This research was conducted at Regional Working Units (SKPD) in the Denpasar City Government with the amount as much as 34 units. The sample used in this study were as many as 44 people SIPKD operator. Quantitative analysis techniques and simple linear regression analysis is used as a data analysis technique. The analysis shows the effectiveness SIPKD in Denpasar city government including the Effective criteria and effective implementation of SIPKD significant effect on the quality of financial reporting in the City of Denpasar.
Keywords: effectiveness, implementation of SIPKD, quality of financial statements